Faktor Individu, Persepsi Risiko, dan Sikap Terhadap Risiko Dalam Keputusan Berinvestasi di Pasar Modal - Hamid Bone; Praja Hadi Saputra (Management Insight: Jurnal Ilmiah Manajemen, 2019)
The investment decision of investor not only based on the financial information provided by the company but also from the individual factors. This statement is a fundamental reason for the scholar to develop a study which observed the individual factors that can affect risk perception and risk attitude on investment decision. This study aims to investigate the effect of individual factors like overconfidence, experience, emotion, and pride on risk perception and risk attitude. The Partial Lease Square (PLS) analysis was applied in this study to test the data and hypotheses. Based on a survey to 43 students from several universities in Samarinda, the results indicate that all of the individual factors in this study have an influence on risk perception and risk attitude in decision-making to involve in capital market trading.